Taxonomy of the Crematogaster degeeri-species-assemblage in the Malagasy region (Hymenoptera: Formicidae) - Blaimer, Bonnie B.; Fisher, Brian L. (European Journal of Taxonomy, 2013)
We revise the species-level taxonomy of the Crematogaster (Crematogaster) degeeri-species-assemblage, a group of related ants occuring in Madagascar and the wider Malagasy region, and further provide an identification key to all species-groups of the genus Crematogaster in this region. Within the C. degeeri-assemblage, we recognize twelve species based upon morphological data from worker, queen and male ants, as well as genetic data from the barcode region of cytochrome oxidase I. Seven new species are described: Crematogaster alafara Blaimer sp. nov., C. bara Blaimer sp. nov., C. mafybe Blaimer sp. nov., C. maina Blaimer sp. nov., C. malahelo Blaimer sp. nov., C. masokely Blaimer sp. nov., C. ramamy Blaimer sp. nov. Crematogaster tricolor Gerstäcker, 1859 (stat. rev.) and C. dentata Dalla Torre, 1893 (stat. nov.) are raised to species level, and the following new synonymies are proposed: Crematogaster degeeri lunaris Santschi, 1928 as a synonym of C. degeeri Forel, 1886; Crematogaster sewelli improba Forel, 1907 and C. sewelli mauritiana Forel, 1907 as synonyms of C. dentata Dalla Torre, 1893, and C. pacifica Santschi, 1919 as a synonym of C. lobata Emery, 1895. Species descriptions, images, and distribution maps and identification keys based on worker ants, as well as on queen ants where available, are presented for all twelve species. In addition, we present a molecular gene tree for cytochrome oxidase I and summarize levels of sequence divergence within and between species of the C. degeeri-species-assemblage. Our findings are discussed in the light of previous work on Malagasy Crematogaster ants.